Pelatihan Pemanfaatan Aplikasi Google Drive dan Google Form Sebagai Instrumen Evaluasi Hasil Belajar Siswa bagi Guru Madrasah Ibtidaiyah Raudlatul Mutaallimin - Sudriyanto Sudriyanto; Novi Fitriani; Dinda Lailatul Qomariyah; Wiwik Widianti (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Education is a key element in the development of society and the nation. Madrasah Ibtidaiyah Raudlatul Mutaallimin Pandean Paiton Probolinggo faces challenges in evaluating student learning outcomes during distance learning. Technological limitations have prompted the search for innovative solutions. The goal of this service effort is to improve the quality of student learning outcome evaluations by utilizing Google Drive and Google Form applications in distance learning. Teachers are empowered through intensive training, workshops, and mentoring, including the use of Google Drive and Google Form in teaching and evaluation question development techniques. Active interaction and knowledge sharing occur during training, which has successfully enhanced teachers' knowledge and skills in creating evaluation instruments with Google Form. The final survey results show a significant improvement, with 87% of respondents experiencing improvement. They are now able to design evaluation instruments more effectively during distance learning. The use of Google Drive and Google Form as evaluation tools opens up opportunities for improving the quality of education. Recommendations for the future include continuing to support teachers, deepening the integration of technology in the learning process, and expanding training to enhance the effectiveness of learning at Madrasah Ibtidaiyah Raudlatul Mutaallimin Pandean Paiton Probolinggo..